2023
DOI: 10.1021/acssuschemeng.2c07622
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of SARS-CoV-2 and Other Enveloped and Non-Enveloped Viruses with Non-Thermal Plasma for Hospital Disinfection

Abstract: As recently highlighted by the SARS-CoV-2 pandemic, viruses have become an increasing burden for health, global economy, and environment. The control of transmission by contact with contaminated materials represents a major challenge, particularly in hospital environments. However, the current disinfection methods in hospital settings suffer from numerous drawbacks. As a result, several medical supplies that cannot be properly disinfected are not reused, leading to severe shortages and increasing amounts of wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…During plasma therapy, plasma provides an extra layer of oxidative stress to limit HSV-1 infection. Thus, plasma has also proved to be a powerful disinfection method for eliminating viruses from hospital equipment and dinnerware (e.g., plastics and fabrics), such as norovirus (NoV), SARS-CoV-2 and Omicron variants, porcine respiratory coronavirus (PRCV), and coxsackievirus B 3 (CVB 3 ) [59,[150][151][152][153].…”
Section: Virusesmentioning
confidence: 99%
“…During plasma therapy, plasma provides an extra layer of oxidative stress to limit HSV-1 infection. Thus, plasma has also proved to be a powerful disinfection method for eliminating viruses from hospital equipment and dinnerware (e.g., plastics and fabrics), such as norovirus (NoV), SARS-CoV-2 and Omicron variants, porcine respiratory coronavirus (PRCV), and coxsackievirus B 3 (CVB 3 ) [59,[150][151][152][153].…”
Section: Virusesmentioning
confidence: 99%
“…This topic became of relevance in reported NTP applications for the decontamination of protective equipment during the pandemic of COVID-19. Several studies were published at this time of lack of protective equipment, mainly face masks and respirators 8 , 9 , 18 20 . In our previous study Obrová et al 8 , we reported that NTP can be advantageously used for the decontamination of respiratory P3 R filters without affecting their filtration capacity.…”
Section: Introductionmentioning
confidence: 99%